The Effect of Water Restriction on Performance and Behaviour of Broiler Breeders - Mohammed, Mustafa Fadil (1998)

(untitled)
A study was carried out to investigate the effect of water restriction on various traits of broiler breeders under tropical conditions. The experimental treatment comprised of water available 24h/d and restricted to 8h/d and 6h/d. Body weight for male and female birds were not affected by water restriction during the growing period. Body weight was reduced significantly during the production period for 6h1d compared with 24h1d but showed no difference with 8h/d. Flock uniformity was similar for all groups at week 21. Water intake was significantly higher in water available ad libitum either on or off feed day compared with restricted groups. Water intake of 8h/d was significantly higher than those on 6h1d on feed day, while there was no significant effect on off feed day. There was no effect of water restriction on the percentage of birds spent standing and walking, resting, preening and spot pecking for all treatments, with the exception of scratching and pecking litter in which the water restricted treatments recorded higher proportion in this activity. Egg production, egg weight and hatchability were reduced significantly by water restriction. Fertility and several defects of egg were not affected by water restriction. Mortality was not affected during rearing, while in production periods mortality was significantly higher in the water restriction treatments. The results of this study showed that water restriction could be used during the growing period, but not during the production periods, since water restriction had a detrimental effect on egg production and mortality.